RISK AND FORMS OF VIOLENCE IN INVESTIGATIVE JOURNALISM WITHIN DIGITAL NATIVE MEDIA: a study of Quinto Elemento and Periodismo de Barrio - Olivera Pérez, Dasniel; Arellano Sánchez, José Refugio (Brazilian journalism research, 2024)
ABSTRACT – Journalism poses inherent dangers for its practitioners and discomforts for those in positions of power around the globe. In response to this concern, this article examines the sources of risk, its manifestations and consequences in "Periodismo de Barrio" and "Quinto Elemento," two digital media outlets focused on investigative journalism in Latin American contexts with distinct political, media, and journalistic risk structures: Mexico and Cuba. Through qualitative interviews with journalists from both outlets, the multidimensional nature of risks is unveiled, alongside the complexity of threats ranging from physical to symbolic violence. The conclusions underscore the dynamic interplay between risk factors and violence against journalists at the social level, the experiential nature of shared perceptions regarding this phenomenon, and the significance of investigative journalism in comprehending the diverse manifestations of violence against journalists. RESUMO – O jornalismo a nível global é uma profissão perigosa para os seus praticantes e desconfortável para os poderes constituídos. Em resposta a esta preocupação, o artigo examina as fontes de risco, suas manifestações e consequências no Periodismo de Barrio e no Quinto Elemento, dois meios digitais orientados ao jornalismo investigativo em contextos latino-americanos com diferentes estruturas políticas, midiáticas e de risco para o trabalho jornalístico: México e Cuba. . Através de entrevistas qualitativas com jornalistas de ambos os meios de comunicação, é revelada a natureza multidimensional dos riscos; bem como a complexidade das ameaças, da violência física à simbólica. As conclusões destacam a inter-relação dinâmica entre os factores de risco e a violência contra jornalistas a nível social, a natureza experiencial das percepções partilhadas sobre este fenómeno e a relevância do jornalismo de investigação para compreender a manifestação de múltiplas formas de violência contra jornalistas. RESUMEN – El periodismo a nivel global es una profesión peligrosa para sus practicantes, e incómoda para los poderes. En respuesta a esta preocupación, el artículo examina las fuentes de riesgo, sus manifestaciones y consecuencias en Periodismo de Barrio y Quinto Elemento, dos medios digitales orientados al periodismo de investigación en contextos latinoamericanos con diferente estructura política, mediática y de riesgos para el trabajo periodístico: México y Cuba. A través de entrevistas cualitativas a los periodistas de ambos medios se revela la naturaleza multidimensional de los riesgos; así como la complejidad de las amenazas, desde la violencia física hasta la simbólica. Las conclusiones destacan la interrelación dinámica entre factores de riesgos y violencias contra los periodistas a nivel social, el carácter experiencial de las percepciones compartidas sobre este fenómeno y la relevancia del periodismo de investigación para entender la manifestación de las múltiples formas de violencia contra los periodistas.